Cuckoo search algorithm for sizing optimization in grid-connected photovoltaic system / Wan Nur Liyana Wan Abd Rahman - Wan Abd Rahman, Wan Nur Liyana (2013)
Cuckoo Search algorithm is a new metaheuristic optimization algorithm that was recently developed by Yang and Deb in year 2009. This paper presented the configuration of a photovoltaic (PV) array of a grid-connected photovoltaic (GCPV) system by using Cuckoo Search (CS) algorithm. The best PV module and inverter that can produce the optimal number of PV modules per strings and the optimal number of parallel PV strings was determined by using CS in order to make the GCPV system produce higher expected annual energy output with the given roof space.